Differences between orthopaedic evaluation and radiological reports of conventional radiographs in patients with minor trauma admitted to the emergency department. Issue 11 (November 2017) - Catapano, Michele; Albano, Domenico; Pozzi, Grazia; Accetta, Riccardo; Memoria, Sergio; Pregliasco, Fabrizio; Messina, Carmelo; Sconfienza, Luca Maria
Abstract: Introduction: During night and on weekends, in our emergency department there is no radiologist on duty or on call: thus, X-ray examinations (XR) are evaluated by the orthopaedic surgeon on duty and reported the following morning/monday by radiologists. The aim of our study was to examine the discrepancy rate between orthopaedists and radiologists in the interpretation of imaging examinations performed on patients in our tertiary level orthopaedic institution and the consequences of delayed diagnosis in terms of patient management and therapeutic strategy. Materials and methods: We retrospectively reviewed all cases of discrepancy between orthopaedists and radiologists, which were categorized according to anatomical location of injury, initial diagnosis and treatment, change in diagnosis and treatment. We used the Chi square test to compare the frequencies of discrepancies between patients ≤14 and >14 years of age. Results: From January to December 2016, 19, 512 patients admitted to our emergency department performed at least an imaging examination; among these patients, 13, 561 underwent XR in absence of an attending radiologist. A discrepant diagnosis was found in 337/13, 561 (2.5%; 184 males; mean age: 36.7 ± 23.7, range 2–95); 151/337 (45%) discrepancies were encountered in the lower limbs, with ankle being the most common site of misdiagnosis (64/151), and 103/337 (30%) in the upper limbs, with the elbow being the most frequent site in this district (35/103). We found 293/337 false negatives (87%) and 44/337 false positives (13%), with 134 and 13 patients needing treatment change, respectively. We found 85/337 discrepancies (25%) in patients ≤14 years of age, and 252/337 (75%) in those >14 years. The distribution of discrepancies per anatomic district was significantly different (P < 0.001) in these two groups of patients. Conclusions: A low rate of discrepancy between orthopaedists and radiologists in evaluating images of patients admitted to our emergency department was found, although treatment change occurred in about half of cases. A thorough and accurate clinical evaluation is crucial to provide a correct treatment and prognosis.